Promoting Mental Health and Well-being in the Digital Age: Exploring the Role of Positive Psychology, Technology and Neuroscience - Dito Anurogo; Benny Novico Zani; Nur Rahmah Awaliah; Janes Sinaga; Teddy Tjahyanto (West Science Interdisciplinary Studies, 2023)
This research study explores the role of positive psychology, technology and neuroscience on the mental health and psychological well-being of students in Jakarta. A mixed methods approach was used, involving quantitative surveys and qualitative interviews with students from different levels of education. Quantitative data analysis showed that engagement in positive psychology interventions was associated with higher levels of psychological well-being and life satisfaction. Excessive social media use showed a negative correlation with mental health outcomes, while moderate and balanced use of technology had no significant impact on well-being. Qualitative analysis highlighted the positive experiences of students participating in the positive psychology intervention and their recognition of the benefits of mindfulness practices. The findings contribute to the understanding of the factors that influence students' mental health and well-being, providing practical insights for educators and policy makers.